2008
DOI: 10.1007/s00264-008-0573-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic urinary tract colonisation predisposes to superficial wound infection in elective orthopaedic surgery

Abstract: There is no evidence surrounding the benefits, effects or clinical outcomes treating asymptomatic urinary tract colonisation. A series of 558 patients undergoing elective admission for orthopaedic surgery were recruited prior to surgery and were screened for urinary tract infection (UTI). Patients had their urine dipstick tested and positive samples were sent for culture and microscopy. Patients with a positive urine culture were treated with antibiotics prior to surgery; 85% of dipsticks tested were positive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 11 publications
2
44
0
3
Order By: Relevance
“…The latest work by Gausden et al (5) showed us how the nonunions of the clavicle are very often related to a latent infection and to saprophytic microorganisms of the surgical site (25). Also from the data collected by us we saw that many patients in the preoperative had a high number of comorbidities and postoperatively had dental treatment or infections of other systems that may have been the source of contamination (26)(27)(28). Therefore it is useful, before proceeding to a surgery for a nonunion, to do a careful history and physical examination to discern what type of symptoms and disability, if any, the patient is experiencing.…”
mentioning
confidence: 87%
“…The latest work by Gausden et al (5) showed us how the nonunions of the clavicle are very often related to a latent infection and to saprophytic microorganisms of the surgical site (25). Also from the data collected by us we saw that many patients in the preoperative had a high number of comorbidities and postoperatively had dental treatment or infections of other systems that may have been the source of contamination (26)(27)(28). Therefore it is useful, before proceeding to a surgery for a nonunion, to do a careful history and physical examination to discern what type of symptoms and disability, if any, the patient is experiencing.…”
mentioning
confidence: 87%
“…[9][10][11][12][13] However, there remains a lack of good evidence that treating asymptomatic bacteriuria reduces the risk of subsequent prosthetic joint infection. Published studies are all small, with insufficient power to generate convincing results.…”
Section: Association Not Causationmentioning
confidence: 99%
“…Otro estudio encontró que los pacientes con infección urinaria asintomática detectada por análisis de 59 orina tenían un mayor riesgo de infección de la herida después de la operación, a pesar del tratamiento . No se 43 encontró evidencia sólida que justifique la realización de análisis de orina en pacientes asintomáticos .…”
Section: Exámenes Laboratorialesunclassified